1990
DOI: 10.1016/0146-6380(90)90106-a
|View full text |Cite
|
Sign up to set email alerts
|

Global comparisons of organic matter in sediments across the Cretaceous/Tertiary boundary

Abstract: A~tract-The Cretaceous/Tertiary (K/T) boundary is marked by extensive changes in the sedimentary fossil record of continental and marine life. Organic matter in sediments from above and below the K/T boundary has been studied to identify consequences of the biotic extinctions and of the changes in biological productivity which occurred at this time. Data from locations encompassing a variety of marine paleoenvironments were examined to assess the global extent and local expressions of these biological changes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…The fact that the shift is absent or lesser in magnitude in the contemporaneous benthos has been interpreted as evidence for the global reduction or shutdown of marine surface primary productivity (the so-called "Strangelove Ocean"; Hsü and McKenzie, 1985;Zachos et al, 1992) and/or a decrease in the flux of organic material from the surface to deep sea (D'Hondt et al, 1998;Alegret et al, 2012) at that time, resulting in the homogenization of the normal surface-to-depth positiveto-negative d 13 C gradient. A similar 1‰-3‰ negative shift in the d 13 C has also been identified across the Cretaceous-Paleogene boundary in organic carbon deposited in marine settings (e.g., Gilmour et al, 1987;Woolbach et al, 1990;Meyers and Simoneit, 1990;Hollander et al, 1993;Arinobu et al, 1999;Yamamoto et al, 2010) and fully terrestrial environments (Schimmelmann and DeNiro, 1984;Beerling et al, 2001;Gardner and Gilmour, 2002;Maruoka et al, 2007;Therrien et al, 2007;Grandpre et al, 2013). Because preserved organic carbon of terrestrial origin records the isotopic composition of the paleoatmosphere (Marino and McElroy, 1991;Jahren et al, 2008), the similarity of the terrestrial and marine d 13 C records has been used to argue for coupling of the atmospheric and shallow-marine carbon reservoirs through the mass extinction event (Beerling et al, 2001).…”
Section: Introductionmentioning
confidence: 52%
“…The fact that the shift is absent or lesser in magnitude in the contemporaneous benthos has been interpreted as evidence for the global reduction or shutdown of marine surface primary productivity (the so-called "Strangelove Ocean"; Hsü and McKenzie, 1985;Zachos et al, 1992) and/or a decrease in the flux of organic material from the surface to deep sea (D'Hondt et al, 1998;Alegret et al, 2012) at that time, resulting in the homogenization of the normal surface-to-depth positiveto-negative d 13 C gradient. A similar 1‰-3‰ negative shift in the d 13 C has also been identified across the Cretaceous-Paleogene boundary in organic carbon deposited in marine settings (e.g., Gilmour et al, 1987;Woolbach et al, 1990;Meyers and Simoneit, 1990;Hollander et al, 1993;Arinobu et al, 1999;Yamamoto et al, 2010) and fully terrestrial environments (Schimmelmann and DeNiro, 1984;Beerling et al, 2001;Gardner and Gilmour, 2002;Maruoka et al, 2007;Therrien et al, 2007;Grandpre et al, 2013). Because preserved organic carbon of terrestrial origin records the isotopic composition of the paleoatmosphere (Marino and McElroy, 1991;Jahren et al, 2008), the similarity of the terrestrial and marine d 13 C records has been used to argue for coupling of the atmospheric and shallow-marine carbon reservoirs through the mass extinction event (Beerling et al, 2001).…”
Section: Introductionmentioning
confidence: 52%
“…However, Ivany and Salawitch (1993) did not include a contribution to atmospheric pCO 2 levels from carbonate in their calculations. No widespread changes in the d 13 C org record between the upper Maastrichtian and lower Paleocene have been observed at marine sites (Meyers and Simoneit, 1990;Meyers, 1992), and the few high-resolution studies of marine organic carbon across the K-T boundary reveal an inconsistent pattern (Gilmour et al, 1987Wolbach et al, 1990). The concomitant changes in d 13 C org org and d 13 C carb at Woodside Creek, New Zealand, have been interpreted as indicating unusual plankton blooms and bacterially dominated degradation of organic matter following decreased photosynthesis (Hollander et al, 1993a).…”
Section: Isotope Excursions and Biotic Crisesmentioning
confidence: 95%
“…Recent research on the K/T boundary sites, in addition to re-evaluation of previously published data increasingly point to another scenario that of progressive and multi-causal mass extinctions as a result of a combination of environmental and climatic factors during the latest Maastrichtian including rapid climate warming followed by rapid cooling (Keller et al 2003). This would have led to highly stressful conditions for marine biota vulnerable to environmental changes (Crowley and North 1988;Meyers and Simoneit 1989;Glasby and Kunzendorf 1996;Keller et al 1998Keller et al , 2003Pardo et al 1999 and references cited therein). Furthermore, many studies have also indicated unequivocally the presence of multiple events predating K/T boundary (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…An abrupt boundary separates the Cretaceous from the Tertiary virtually everywhere in the global stratigraphic record (Meyers and Simoneit 1989). Consensual explanation for this major perturbation remains elusive, notwithstanding considerable discussions from a large part of the earth science community (e.g.…”
Section: Introductionmentioning
confidence: 99%